Transcriptomic and proteomic mechanisms underlying cold tolerance in plants - K. JAMSHIDI GOHARRIZI; S. KARAMI; T. BASAKI; M. MOSTAFAEI DEHNAVI; M.A. NEJAT; M.M. MOMENI; G. MERU (Biologia Plantarum, 2022)
Abiotic stress is one of the major challenges facing crop production globally. Abiotic stress resulting from low temperature is a major limitation to crop production, especially in the temperate regions of the world. Cold stress not only influence crop development and reduce yields, but also curtail the efficient distribution of agricultural products worldwide. An understanding of the molecular mechanisms underlying cold stress tolerance is important for the development of strategies to manage crop loss and improve yield. In this review, we explore the major molecular mechanisms involved in plant cold tolerance, including recent discoveries on interrelated gene networks and regulatory mechanisms for cold stress adaptation in crops. Further, we highlight the role of proteomics in the discovery of proteins involved in key signaling pathways, including late embryogenesis-abundant proteins, antifreeze proteins, cold-regulated proteins, heat shock proteins, and pathogenesis-related proteins. The role of these proteins, and their relative abundance in physiological-biochemical reactions, are discussed and key candidate proteins for plant genetic enhancement are suggested.